2018
DOI: 10.1007/s00421-018-3912-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peak oxygen uptake and exercise efficiency between upper-body poling and arm crank ergometry in trained paraplegic and able-bodied participants

Abstract: PurposeTo compare peak oxygen uptake (VO2peak) and exercise efficiency between upper-body poling (UBP) and arm crank ergometry (ACE) in able-bodied (AB) and paraplegic participants (PARA).MethodsSeven PARA and eleven AB upper-body trained participants performed four 5-min submaximal stages, and an incremental test to exhaustion in UBP and ACE. VO2peak was the highest 30-s average during the incremental test. Metabolic rate (joule/second = watt) at fixed power outputs of 40, 60, and 80 W was estimated using lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
(41 reference statements)
2
18
0
Order By: Relevance
“…This is contrary to our hypothesis and might suggest that trunk oscillations and shifts in center of gravity, that contribute more to propulsion in the WTR compared to the ACE mode (Vanlandewijck et al, 2001), do not necessarily lead to a larger active muscle mass with a consequently higher VO 2peak . In line with the other mode comparisons in the current review, Arabi et al (1997) found no difference in VO 2peak between WERG and WTR and Baumgart et al (2018b) found no difference in VO 2peak between ACE and UBP or between WERG and WTR. However, our ability to conclude with certainty is limited due to the wide CIs of the overall effect, the limited to moderate LoE and the limited amount of studies included for these comparisons.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This is contrary to our hypothesis and might suggest that trunk oscillations and shifts in center of gravity, that contribute more to propulsion in the WTR compared to the ACE mode (Vanlandewijck et al, 2001), do not necessarily lead to a larger active muscle mass with a consequently higher VO 2peak . In line with the other mode comparisons in the current review, Arabi et al (1997) found no difference in VO 2peak between WERG and WTR and Baumgart et al (2018b) found no difference in VO 2peak between ACE and UBP or between WERG and WTR. However, our ability to conclude with certainty is limited due to the wide CIs of the overall effect, the limited to moderate LoE and the limited amount of studies included for these comparisons.…”
Section: Discussionsupporting
confidence: 86%
“…One study compared body-mass normalized VO 2peak between the WERG and the WTR mode and found no difference (Arabi et al, 1997) (LoE: limited). In addition, one study compared absolute and body-mass normalized VO 2peak between the ACE and the UBP mode and found no difference (Baumgart et al, 2018b) We were only able to investigate the influence of body mass and participant-related characteristics on differences in FIGURE 3 | ES, Effect size (95% CI range) of the difference in (A) absolute and (B) body-mass normalized VO 2peak between the arm crank ergometer vs. wheelchair ergometer mode. The dot size indicates the relative weight of each study in determining the overall effect size.…”
Section: Meta-analyses: Comparison Of Vo 2peak Between Modesmentioning
confidence: 98%
See 2 more Smart Citations
“…VT. USA). The equipment used to assess body mass, as well as respiratory parameters, BLa and RPE during the incremental test in accordance with Baumgart et al ( 2018b ). HR was assessed with the same Garmin Forerunner 920XT used during the outdoor testing.…”
Section: Methodsmentioning
confidence: 99%